PREVENTION OF SELF-HARM AND SUICIDE IN ADOLESCENTS - Istriana, Erita (Faculty of Medicine, Trisakti University, 2020)
Adolescence is a transitional stage in physical and psychological development, and in this stage multiple physical, emotional and social changes, can make adolescents vulnerable to mental health problems like self-harm and suicide. Self-harm and suicide are serious problems in children, adolescents and young people with the highest rates seen in those aged 16-24 years, and self-harm is highly correlated with the presence of anxiety disorders and depression.